Power of Culture : Driving Todays Organisation - Power of Culture
In the Power OF Culture, the Australian Institute Of Management drwas together nine accomplishied managers and business experts to explore the implications and applications of organisational culture, including how to understand, assess, manage and lead organisation culture toachieve competitive advantage.